Barriers to social reconstruction of communities in the aftermath of organized violence - Ajduković, Dean (Array, 2004)
War or massive terrorist attacks have distinct characteristics that disrupt social patterns, challenge the existing social institutions, may lead to shift in social structure, question the social norms and value systems, and destabilize communities in other ways. Likewise, the social milieu in which lives of survivors of armed conflicts are embedded has important consequences for individual and community recovery. Better understanding of interpersonal, intra- and inter-group processes can help us design interventions that may facilitate recovery from massive suffering in a war. Our studies clearly identified interpersonal processes that lead to loss of mutual trust, disruption of norms and decreasing quality and efficiency in close social transactions. The task of effective community-based interventions is to help facilitate psychosocial reconstruction of the communities, decrease social tensions among groups that have been involved in a conflict, provide treatment for the most traumatized individuals and work towards re-connecting community members. The key process that may be conductive to such recovery at the community level is the social reconstruction. We see individual recovery from violence and community social reconstruction as two parallel, interdependent and non-linear processes.